OPTIMIZING FINANCIAL LITERACY, DIGITAL BANKING, AND ACCOUNTING SYSTEMS TO SUPPORT BUSINESS SUSTAINABILITY THROUGH IMPROVED FINANCIAL REPORTING IN BALI PROVINCE - Andriani Pratiwi, I Gusti Ayu Made Agung Mas (Universitas Mercu Buana Yogyakarta, 2025)
Micro, Small and Medium Enterprises are the central pillar of regional economies but remain vulnerable to economic fluctuations. The quality of financial statements reflects business conditions and serves as a strategic tool for decision-making, financing access, and partnerships. Amid efforts for economic recovery and digital transformation in Bali, strengthening the quality of financial reporting has become a priority to sustain MSME operations. This study aims to analyze the influence of financial literacy, digital banking, and accounting information systems on the sustainability of MSMEs, with financial reporting quality as a mediating variable. A quantitative approach was employed using purposive sampling. Primary data were collected from 100 MSME actors in Bali Province who have adopted accounting information systems and digital banking. Data analysis was performed using Microsoft Excel and SmartPLS. The results show that financial literacy, digital banking, and accounting information systems have a positive and significant effect on financial reporting quality. Financial literacy and financial reporting quality significantly influence business sustainability, while digital banking and accounting information systems do not. Financial reporting quality mediates the effects of digital banking and accounting information systems but does not mediate the impact of financial literacy. Support from local governments and academics is needed to strengthen financial literacy and technology adoption, ensuring that MSMEs remain sustainable, resilient, and competitive.